Pengaruh Media Sosial Instagram Terhadap Gaya Hidup Mahasiswa Fakultas Ilmu Komunikasi Universitas Mercu Buana Yogyakarta - Khalifi Arrahman; Muhamad Nastainb (CV. ITTC INDONESIA, 2023)
The development of technology and information is currently changing many aspects of people's lives. The emergence of social media as one sign of technological advancement has changed the lifestyle behavior of people. For some people, lifestyle is important for self-expression. The purpose of this study is to illustrate the lifestyle of students in the Faculty of Communication Sciences at Mercu Buana University of Yogyakarta after social media on Instagram. This study uses descriptive and quantitative methods. This approach explains how Instagram social media affects students' lifestyles. The tool used by researchers is a questionnaire. The survey asked for information about the effects of Instagram on student behavior and respondents' reactions to their current use of Instagram.